The Hegemony Practices of Indigenous Agencies in the Settlement of Violence against Women in Sigi Regency - Fadhliah Fadhliah; Musta’in Musta’in; Santi Isnaini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This research seeks to uncover the thegemony practices of indigenous agencies in the settlement of violence against women in Sigi District. Customary institutions are the people's choice in solving social problems, especially violence against women. This shows that the control or hegemony of adat institutions is so strong in influencing decisions or functioning as a mediator in problem solving. In addition, the use of interpersonal communication strategies that are practiced in the implementation of the hegemony of traditional institutions in resolving cases of violence against women. This study uses a qualitative method based on a critical ethnographic approach. The findings of this research are, first, the practice of traditional institution hegemony proved effective in resolving social cases, especially violence experienced by women. The adat institution functions as a mediator like a community without going through a normative judicial process. Second, the Pabbisara Ada Adat Institution 'has significant strength in solving interpersonal problems in the Sigi region through interpersonal communication. This research implies that through interpersonal communication tools, hegemonic practices are persuasively persecuted. This means that this form of communication has a very significant role in realizing the harmony of communication between people of different ethnic backgrounds. Hegemony is achieved because adat institutions work effectively both directly and indirectly, aimed at evaluating problematic social realities. The practice of hegemony with the interpersonal communication approach is considered effective for resolving violence